Economic Analysis of Cattle Breeding around the Recently Created Dairy Basin in the Hodh Chargui Region, South-Eastern Mauritania - Youssouf El Hadj; Sidi Hamady; Saad Bouh Sidaty; Ali Ould Mohamed Salem Boukhary; M’Naouer Djemali; Mohamed Ould Ahmed (Biology and Life Sciences Forum)
(1) Background: Milk is an important product in Mauritania both for livelihood and food and nutritional security. (2) Methods: In this study, we examine the economic performance of cattle farms in the Hodh Chargui region using data from a cross-sectional survey of 50 farms conducted in 2023. (3) Results: The results showed that the most significant cost item was animal feed (54%), followed by labor (40%) and charges induced by health and watering (3% each). In terms of income, the sale of young males accounted for the largest portion (48%), followed by the sales of dry cows (20%), lactating cows (17%), adult males (8%), and milk (7%). The average gross margin was MRU 131,697.82 ± 509,571.84 (equivalent to USD 3300.69 ± 12,771.22) per breeder per year. Out of the farms surveyed, 46% (23/50) reported a positive gross margin, while 54% reported a negative gross margin. (4) Conclusions: These results indicate a wide range of profitability, from lowest to highest, and suggest the need for improved management of cattle farms in Hodh Chargui in order to enhance their economic efficiency.